Managing and Adapting a development program: Lessons from PRISMA - and Seely, Kevin (PRISMA, 2019)
This case study is part of the AIP-Rural Learning Series. Funders and implementers of international development programs largely agree that adaptive management is industry best practice. Most development experts also broadly agree on what ‘adaptive management’ means. In this case study, we use a common definition of ‘adaptive management’, including the following features: Flexibility. Implementers create, modify and drop interventions when circumstances change or new information emerges, in order to tailor strategies to context and maximise impact. Purposeful experimentation. Implementers test different activities at the same time, monitoring them to learn what will achieve the desired impact. Since 2015, the number of publications calling for and praising adaptive management in development programs has grown fast. These publications give us an idea of the state of adaptive management in development programs. They reveal progress in some areas, such as tailoring interventions to local context and using evidence for decision-making. Yet they also reveal multiple, ongoing, real-world constraints to adaptive management. This case study explores how one development program, PRISMA, has avoided and overcome some of these constraints, whilst continuing to battle others. Four major constraints revealed in the adaptive management literature are discussed in this case study: Programs are designed in ways that make it hard to adapt interventions, target regions or sectors based on new learning or changing circumstances. Programs struggle to create an organisational culture that encourages learning and adapting. When staffing programs, recruiters prioritise sectoral expertise and length of experience over adaptive managerial competence. Program managers face pressures to spend their budgets predictably and before their program ends. Learning and testing take time and cost little, so managers feel pressure to deprioritise them. The first of these constraints is explored in the next section, ‘Design’, which looks at how the selection of target sectors and performance targets affects PRISMA implementers’ ability to manage adaptively. The third section, ‘Organisational Culture’, shares lessons on encouraging staff to test and improve interventions. Section 4, ‘Staffing’, looks at hiring adaptive managers, and freeing up their time to improve interventions. The final section summarises this case study’s key lessons. Throughout this paper, findings are based on 16 in-depth interviews with PRISMA’s junior, mid-level and senior staff, and its funders. To contextualise these findings, the authors reviewed the ‘adaptive management’ literature, and drew on their experience with development programs worldwide.